Use of generic and essential medicines for prevention and treatment of cardiovascular diseases in Portugal - Helena Gama; Carla Torre; José Pedro Guerreiro; Ana Azevedo; Suzete Costa; Nuno Lunet (BMC, 2017)
Abstract Background The successful control of cardiovascular diseases at the lowest possible cost requires the use of the most effective and affordable medicines. We aimed to describe the trends in the ambulatory use of medicines for prevention and treatment of cardiovascular diseases [Anatomic Therapeutic Chemical classification system (ATC): C and B01A] in Portugal, between 2004 and 2012, and to estimate the potential for expenditure reduction through changes in patterns of use. Methods We analysed sell-out data, expressed as defined daily doses (DDD) and pharmacy retail price (€), from a nationwide database. We estimated potential reduction in expenditures through the increase, up to 90% of the volume of DDD, in the use of generic and essential medicines; the latter were defined according to guidelines from Portugal and another European country. Results Overall consumption increased by approximately 50% from 2004 to 2012, reaching nearly 2400 million DDD, whereas expenditure decreased to 753 million € (−31.3% since 2006). Use of generics and essential medicines increased, representing 43.6 and 39.9% of DDD consumption in 2012, respectively. The 40 most used groups of medicines in 2012 accounted for just over 80% of overall consumption; among these, increase in use of generics and essential medicines would have contributed to a saving of 275 million €. Conclusions Changes in patterns of consumption of medicines towards a more frequent use of generics, a preferential use of essential medicines and a more rational use of fixed-dose combinations may contribute to a more efficient use of health resources.